2010
DOI: 10.1016/j.jchromb.2010.09.033
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic studies of changes in binding of sulfonylurea drugs to human serum albumin due to glycation and fatty acids

Abstract: This report examines the use of high-performance affinity chromatography as a screening tool for studying the change in binding by sulfonylurea drugs to the protein human serum albumin (HSA) during diabetes. The effects of both the non-enzymatic glycation of HSA and the presence of fatty acids on these interactions were considered using a zonal elution format. It was found that there was significant increase (i.e., 2.7 to 3.6-fold) in the relative retention of several sulfonylurea drugs (i.e., acetohexamide, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
38
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 26 publications
7
38
0
1
Order By: Relevance
“…The extent of glycation is known to increase during diabetes, with the amount of glycated HSA increasing by 2- to 5-fold for diabetic patients versus normal individuals [17]. It has been suggested that this type of modification can alter the binding of some drugs or solutes to HSA [1823]. Another change that can occur during diabetes is an elevation in the levels of fatty acids in serum.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…The extent of glycation is known to increase during diabetes, with the amount of glycated HSA increasing by 2- to 5-fold for diabetic patients versus normal individuals [17]. It has been suggested that this type of modification can alter the binding of some drugs or solutes to HSA [1823]. Another change that can occur during diabetes is an elevation in the levels of fatty acids in serum.…”
Section: Introductionmentioning
confidence: 99%
“…High-performance affinity chromatography (HPAC) and columns containing normal HSA or glycated HSA were recently used to compare the overall effects of glycation and fatty acids on the binding of HSA with several sulfonylurea drugs [18,19]. Each of these drugs is known to have multisite binding to both normal HSA and glycated HSA and to interact at both Sudlow sites I and II [10,18,19,21,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In turn, addition of organic modifier can accelerate the elution of analyte by disturbing the hydrophobic interactions (Hage & Chen, 2006). It also allows to examine the change in binding of drugs when standard physiological system conditions will be changed as a result of pathological lesions (Basiaga & Hage, 2010).…”
Section: Zonal Chromatographic Studies Of Drug-protein Bindingmentioning
confidence: 99%